Andinodarnis gen. nov., a new treehopper genus from the Andes (Hemiptera: Membracidae: Darninae) - Flórez-V, Camilo; Evangelista, Olivia (Zootaxa, 2022)
Andinodarnis gen. nov. (Darninae: Darnini) is proposed based on recently collected treehoppers from the Northern Andes. The new genus includes two species, Andinodarnis pectoralis (Stål, 1869) comb. nov. (= Tomogonia pectoralis Stål, 1869) and Andinodarnis atromeris sp. nov. (PNN Tatamá, Cordillera Occidental, Colombia). Identification keys, annotated diagnoses, life history records, illustrations, and distribution maps are provided for both species with new distribution records from Ecuador.